In Vitro and In Silico Antidiabetic and Antimicrobial Evaluation of Constituents from Kickxia ramosissima (Nanorrhinum ramosissimum) - Amin, Adnan; Tuenter, Emmy; Foubert, Kenn; Iqbal, Jamhsed; Cos, Paul; Maes, Louis; Exarchou, Vassiliki; Apers, Sandra; Pieters, Luc (Frontiers in Pharmacology, 2017)
Background and Aims: Kickxia ramosissima (Wall.) Janch (or Nanorrhinum ramosissimum (Wall.) Betsche is a well-known medicinal plant in Pakistan that is traditionally used in diabetic and inflammatory conditions. Because little information is available on its phytochemical composition, a range of constituents were isolated and evaluated in vitro in assays related to the traditional use. Methods: Dried whole plant material was extracted and chromatographically fractionated. Isolated constituents were evaluated in silico and in vitro in assays related to the traditional use against diabetes (inhibition of α-glucosidase activity; inhibition of Advanced Glycation Endproducts - AGEs) and in inflammatory conditions (inhibition of AAPH induced linoleic acid peroxidation, inhibition of 15-LOX, antimicrobial activity). Results: Phytochemical analysis of the extracts and fractions led to isolation of 7 compounds, including the iridoids kickxiasine (being a new compound), mussaenosidic acid, mussaenoside and linarioside; the flavonoids pectolinarigenin and pectolinarin; and 4-hydroxy-benzoic acid methyl ester. The iridoids showed weak antiglycation activity. The flavonoids, however, showed interesting results as pectolinarigenin was highly active compared to pectolinarin. In the α-glucosidase inhibition assay, only weak activity was observed for the iridoids. However, the flavonoid pectolinarigenin showed good activity, followed by pectolinarin. In the 15-LOX experiment, moderate inhibition was recorded for most compounds, the iridoids mussaenosidic acid and mussaenoside being the most active. In the AAPH assay, weak or no inhibition was recorded for all compounds. The in silico assays for the α-glucosidase and 15-LOX assays confirmed the results of respective in vitro assays. Pectolinarigenin showed moderate antimicrobial activity against Staphylococcus aureus, Plasmodium falciparum K1 and Trypanosoma cruzi, but it was not cytotoxic on a human MRC-5 cell line. Conclusions: Based on our findings the tradtional use of K. ramosissima could at least in part be confirmed.